The reality of media freedom in Swaziland under the new constitutional dispensation - Hlatshwayo, Vuyisile Sikelela (Centre for Film and Media Studies, 2015)
The study concludes that there is still lack of media freedom in Swaziland under the new constitutional dispensation. Its significant finding is that the lack of media freedom is a consequence of constitutional, legal and extra-legal constraints.